Determining Factors of Peer-to-Peer (P2P) Lending Avoidance: Empirical Evidence from Indonesia - Syaiful Ali; Billy Simboh; Ulfa Rahmawati (Gadjah Mada International Journal of Business, 2023)
P2P lending offers loans to the public with easy processes and terms. However, the level of P2P lending disbursements is still lower than that of the banks. In addition, a comparison of the number of users of P2P lenders and the productive age population of Indonesia shows that there are still many people who do not use P2P lending. This paper examines the factors that make Indonesians avoid P2P lending. This study used an online survey approach for its data collection and structural equation modeling (SEM) to analyze the data from 499 responses. The study found that the perceived threat from P2P lending is influenced by its perceived severity, perceived susceptibility, and risk tolerance. This perceived threat and social influences cause people’s avoidance motivation. This study contributes to the fintech literature by providing empirical evidence on the avoidance of P2P lending from the borrowers’ perspectives using the TTAT model. Other implications are an input for regulators/governments to enforce the rules for user protection and input for the P2P lending service providers to provide educational programs regarding the use of P2P lending.